2002
DOI: 10.1046/j.1365-2168.2002.02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic pathways involved in the progression of Barrett's metaplasia to adenocarcinoma

Abstract: The main genetic alterations accompanying the progression through dysplasia to adenocarcinoma were collated from 135 papers. The principal genetic changes implicated are the loss of p16 gene expression (by deletion or hypermethylation), the loss of p53 expression (by mutation and deletion), the increase in cyclin D1 expression, the induction of aneuploidy and the losses of the Rb, DCC and APC chromosomal loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 94 publications
4
93
1
4
Order By: Relevance
“…Like in breast carcinoma, mutations of the p53 gene appear to play an important role in the development of oesophageal squamous cell carcinoma, dysplastic Barrett's epithelium and the progression to oesophageal adenocarcinoma (Casson et al, 1991;Neshat et al, 1994;Wu et al, 1998). Ample studies have reported mutations in p53 in oesophageal carcinomas, with mutation frequencies varying from 40 to 90% (Jankowski et al, 1999;Mandard et al, 2000;Wijnhoven et al, 2001;Jenkins et al, 2002). As CHEK2 and p53 are thought to be participants of the same biological pathway, we aimed to establish whether CHEK2*1100delC confers susceptibility to oesophageal cancer, by determining the frequency of the mutation among an unselected series of oesophageal cancers and precursor lesions.…”
mentioning
confidence: 99%
“…Like in breast carcinoma, mutations of the p53 gene appear to play an important role in the development of oesophageal squamous cell carcinoma, dysplastic Barrett's epithelium and the progression to oesophageal adenocarcinoma (Casson et al, 1991;Neshat et al, 1994;Wu et al, 1998). Ample studies have reported mutations in p53 in oesophageal carcinomas, with mutation frequencies varying from 40 to 90% (Jankowski et al, 1999;Mandard et al, 2000;Wijnhoven et al, 2001;Jenkins et al, 2002). As CHEK2 and p53 are thought to be participants of the same biological pathway, we aimed to establish whether CHEK2*1100delC confers susceptibility to oesophageal cancer, by determining the frequency of the mutation among an unselected series of oesophageal cancers and precursor lesions.…”
mentioning
confidence: 99%
“…Despite advances in treatment of EAC, its prognosis is still poor (Falk, 2002). The molecular basis of the development of EAC, although extensively studied (Jenkins et al, 2002;Brabender et al, 2004;McManus et al, 2004;Metzger et al, 2004), is not completely understood. Better understanding of the molecular alterations during its development might improve prevention and tumor control and ultimately lead to better disease management.…”
Section: Introductionmentioning
confidence: 99%
“…The genes involved in the development of Barrett's metaplasia seem to be: p16, APC, Rb, p53, DCC which are lost in this early step. Moreover, cyclin D1 could be amplified, p53 mutated, APC hypermethylated and Bcl2, iNOS, COX-2, CDX2, SRC, SKI, SnoN overexpressed (9)(10)(11).…”
Section: From Metaplasia To Adenocarcinomamentioning
confidence: 99%
“…Aneuploidy has been detected in ADC, dysplastic tissue and metaplastic Barrett's epithelium (13) but others authors suggested that aneuploidy characterizes more the dysplastic and the tumor development then the metaplastic step (14). Cell signalling genes such as HER-2 (also called ERBB2, HER-2/neu, NEU), EGFR, TGFa gene, Kras seems to be overexpressed/amplified in adenocarcinomas arisen in BE but not in metaplasia, appearing to be a late event (9,15). Conversely, TFF1, MUC5AC, meprin A and sucrose isomaltase are always positive in non dysplastic BE and negative in dysplasia (16).…”
Section: From Metaplasia To Adenocarcinomamentioning
confidence: 99%
See 1 more Smart Citation